Effect of menopause on cerebral artery blood flow velocity and cerebrovascular reactivity: Systematic review and meta-analysis. (June 2021) - Ruediger, Stefanie L; Koep, Jodie L; Keating, Shelley E; Pizzey, Faith K; Coombes, Jeff S; Bailey, Tom G
Highlights: This systematic review and meta-analysis revealed no significant difference in cerebral blood flow between pre- and post-menopausal women. We observed a low certainty of evidence for the effect of menopause on reductions in cerebral blood flow in post- compared with pre-menopausal women. The effect of menopausal status on cerebrovascular function, as measured by cerebrovascular reactivity, is inconclusive. Comprehensive research into the effects of the menopausal transition on cerebral blood flow and function is warranted. Research must include adherence to STRAW+10 reporting criteria of menopausal status to characterise potential changes in cerebrovascular function during and after menopause. Abstract: Background: Menopause and its associated decline in oestrogen is linked to chronic conditions like cardiovascular disease and osteoporosis, which may be difficult to disentangle from the effects of ageing. Further, post-menopausal women are at increased risk of cerebrovascular disease, linked to declines in cerebral blood flow (CBF) and cerebrovascular reactivity (CVR), yet the direct understanding of the impact of the menopause on cerebrovascular function is unclear. The aim of this systematic review and meta-analysis was to examine the literature investigating CBF and CVR in pre- compared with post-menopausal women Methods: Five databases were searched for studies assessing CBF or CVR in pre- and post-menopausal women. Meta-analysis examined the effect of menopausal status on middle cerebral artery velocity (MCAv), and GRADE-assessed evidence certainty Results: Nine studies (n=504) included cerebrovascular outcomes. Six studies (n=239) reported negligible differences in MCAv between pre- and post-menopausal women [2.11cm/s (95% CI: -8.94 to 4.73, p=0.54)], but with a "low" certainty of evidence. MCAv was lower in post-menopausal women in two studies, when MCAv was adjusted for blood pressure. CVR was lower in post- compared with pre-menopausal women in two of three studies, but high-quality evidence is lacking. Across outcomes, study methodology and reporting criteria for menopause were inconsistent Conclusions: MCAv was similar in post- compared with pre-menopausal women. Methodological differences in characterising menopause and inconsistent reporting of cerebrovascular outcomes make comparisons difficult. Comprehensive assessments of cerebrovascular function of the intra- and extracranial arteries to determine the physiological implications of menopause on CBF with healthy ageing is warranted.